Cardiovascular Phenotypic Spectrum of 1p36 Deletion Syndrome - Kaur, Tripat; Sriram, Chenni S.; Prasanna, Priyanka; Kohli, Utkarsh (Journal of Pediatric Genetics, 2021)
Chromosome 1p36 deletion syndrome is a common genetic anomaly (prevalence: 1 in 5,000–1 in 10,000). Despite reports of cardiovascular involvement, the cardiovascular phenotypic spectrum of patients with 1p36 deletion syndrome is not well characterized. In this article, we reported the clinical course of a full-term African American boy with chromosome 1p36 deletion syndrome and neonatal onset of severe cardiac disease with moderate-to-severe biventricular dysfunction and severe pulmonary hypertension. Early neonatal onset presentation of 1p36 deletion syndrome is rare and might be associated with a more guarded prognosis. This case based study is supplemented by a comprehensive review of cardiovascular involvement in this relatively common genetic syndrome.
Keywords: 1p36 deletion; congenital heart disease; pulmonary hypertension; noncompaction cardiomyopathy; dilated cardiomyopathy